Monogenic diabetes in overweight and obese youth diagnosed with type 2 diabetes: the TODAY clinical trial - Kleinberger, Jeffrey W; Copeland, Kenneth C; Gandica, Rachelle G; Haymond, Morey W; Levitsky, Lynne L; Linder, Barbara; Shuldiner, Alan R; Tollefsen, Sherida; White, Neil H; Pollin, Toni I (Genetics in medicine, 2018)
Purpose Monogenic diabetes accounts for 1–2% of diabetes cases. It is often undiagnosed, which may lead to inappropriate treatment. This study was performed to estimate the prevalence of monogenic diabetes in a cohort of overweight/obese adolescents diagnosed with type 2 diabetes (T2D). Methods Sequencing using a custom monogenic diabetes gene panel was performed on a racially/ethnically diverse cohort of 488 overweight/obese adolescents with T2D in the Treatment Options for Type 2 Diabetes in Adolescents and Youth (TODAY) clinical trial. Associations between having a monogenic diabetes variant and clinical characteristics and time to treatment failure were analyzed. Results More than 4% (22/488) had genetic variants causing monogenic diabetes (seven GCK , seven HNF4A , five HNF1A , two INS , and one KLF11 ). Patients with monogenic diabetes had a statistically, but not clinically, significant lower body mass index (BMI) z -score, lower fasting insulin, and higher fasting glucose. Most (6/7) patients with HNF4A variants rapidly failed TODAY treatment across study arms (hazard ratio = 5.03, P = 0.0002), while none with GCK variants failed treatment. Conclusion The finding of 4.5% of patients with monogenic diabetes in an overweight/obese cohort of children and adolescents with T2D suggests that monogenic diabetes diagnosis should be considered in children and adolescents without diabetes-associated autoantibodies and maintained C-peptide, regardless of BMI, as it may direct appropriate clinical management.